Evaluation of meniscal changes in two models of knee osteoarthritis: traumatic loading and modified transection - Fischenich, Kristine Marie, author; Haut Donahue, Tammy, advisor; Donahue, Seth, committee member; Goodrich, Laurie, committee member (Colorado State University. Libraries, 2013)
Osteoarthritis (OA) is a debilitating joint disease characterized by the erosion of articular cartilage on the ends of long bones, causing painful bone on bone contact. OA can affect any joint but is commonly seen in the knee and is a major cause of disability. Normally thought of as a degenerative disease, the early onset of OA can be triggered by a number of factors including injury to the joint. With the number of younger athletes increasing as well as the incidence of knee injury increasing it is important to understand the development and progression of post traumatic OA (PTOA). Only then can measures be taken to prevent, or slow the progression. The most common method to study PTOA of the knee involves using an animal model where the anterior cruciate ligament is transected (ACLT). The ACLT model fails to account for a number of factors that are commonly seen in clinical cases. The compressive forces experienced by the joint as well as damage to other joint structures are not accounted for in the tradition ACLT model. Furthermore, despite the well documented role of the meniscus in joint stability and joint kinematics other tissues such as the articular cartilage and subchondral bone have received more attention. PTOA is a "whole organ" disease where damage to one structure influences other structures, and in order to fully understand the progression the entire joint must be studied. There is a lack of knowledge as to how the meniscus is both affected and influences the development of OA. To better understand its role there have been two PTOA models developed for this study. The first is a modified ACLT model (mACLT), where meniscal damage is surgically induced at the time of ACL transection. The second model is a traumatic tibiofemoral compressive impact model (ACLF) where the ACL is ruptured due to a blunt force trauma to the joint. The objective of this thesis was to monitor meniscal changes twelve weeks following impact for both the mACLT and ACLF model. Meniscal damage was monitored over time with the use of magnetic resonance imaging MRI. At dissection gross morphology was graded and compared to the acute and chronic MRI notes. Each meniscus was then sectioned into regions and mechanically tested. Indentation relaxation testing allowed for the instantaneous as well as equilibrium elastic moduli to be calculated. Following mechanical testing meniscal tissue was fixed and stained for glycosaminoglycan (GAG) content. Using semi qualitative analysis, the GAG intensity and coverage was analyzed. Acute and chronic damage, elastic moduli, and GAG content from the injured limbs was then compared to the contralateral controls.
Keywords: impact; transection; trauma; osteoarthritis; meniscus